2005
DOI: 10.1039/b407947g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intramolecular π–π and CH–π interactions between ligands on structure, electrochemical and spectroscopic properties of fac-[Re(bpy)(CO)3(PR3)]+(bpy = 2,2′-bipyridine; PR3= trialkyl or triarylphosphines)

Abstract: Intramolecular pi-pi and CH-pi interactions between the bpy and PR3 ligands of fac-[Re(bpy)(CO)3(PR3)]+ affect their structure, and electrochemical and spectroscopic properties. Intramolecular CH-pi interaction was observed between the alkyl groups on the phosphine ligand (R =nBu, Et) and the bpy ligand, and intramolecular pi-pi and CH-pi interactions were both observed between the aryl group(s) on the phosphorus ligand (R =p-MeOPh, p-MePh, Ph, p-FPh, OPh) and the bpy ligand, while no such interactions were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 63 publications
8
66
0
1
Order By: Relevance
“…To cancel the electronic effect, we can use Tol- mans c values, which are used as an index of the electronaccepting ability of phosphine ligands. [21,22,29] Figure 12a and b show the relationships of the oxidation potential E On the other hand, the redox potential attributed to reduction of the dmb ligand did not show a simple linear correlation with the Sc value, as shown in Figure 12b. We have reported that through-space interaction between the diimine ligand and the aryl group(s) in the phosphine ligands of fac-…”
Section: Structural Features Of Eta C H T U N G T R E N N U N G (Nm)mentioning
confidence: 78%
See 2 more Smart Citations
“…To cancel the electronic effect, we can use Tol- mans c values, which are used as an index of the electronaccepting ability of phosphine ligands. [21,22,29] Figure 12a and b show the relationships of the oxidation potential E On the other hand, the redox potential attributed to reduction of the dmb ligand did not show a simple linear correlation with the Sc value, as shown in Figure 12b. We have reported that through-space interaction between the diimine ligand and the aryl group(s) in the phosphine ligands of fac-…”
Section: Structural Features Of Eta C H T U N G T R E N N U N G (Nm)mentioning
confidence: 78%
“…Synthesis of the rhenium(I) complexes EtA C H T U N G T R E N N U N G (n,m): The bisphosphine rhenium(I) complexes EtA C H T U N G T R E N N U N G (n,m) were synthesized through mono-phosphine-tricarbonyl-rhenium(I) complexes by the photoinduced ligand substitution reaction [21] as shown in Scheme 2. These complexes were isolated as the PF 6 À salts and purified by column chromatography on silica gel and/or recrystallization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ligands coordinated to a metal, can interact with a π-system. In addition, interactions named metal-ligand-aromatic cation-π interactions (MLACπ) [14][15][16][17][18][19], can be considered as a type of XH/π hydrogen bond [20][21][22]. It was shown that some of these interactions are among the strongest XH/π hydrogen bonds [18].…”
Section: Introductionmentioning
confidence: 99%
“…are the subject of intensive study as a new approach of developing materials science [1]. In coordination chemistry, these weak interactions are important in determining the conformations, the selectivities of the reactions, and the crystal structures of metal complexes [2]. The p -p and CH -p interactions are noncovalent forces which contribute to self-assembly and/or recognition processes when extended structures are formed from building blocks with aromatic moieties [3].…”
mentioning
confidence: 99%